1975
DOI: 10.1002/pssa.2210320253
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Magnetic Ordering in Fine Gadolinium Particles

Abstract: We have studied the effect of the size of gadolinium particles on their structure and magnetic properties. Particle sizes varied within the range from 1000 to 200 g. X-ray diffraction investigations showed that the structure of fine gadolinium particles can be presented a s a three-phase mixture: a hexagonal close-packed ( h . c . p . ) phase, fully corresponding to the lattice of the gadolinium bulk sample, and two face centered cubic (f. c . c. ) phases with the parameters a = ( 5 . 3 2 1 and a = 5 . 3 9 2 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…More interestingly, they have shown a size-induced structural transformation from the hexagonal (typical of bulk Gd) to a cubic fcc structure in the 5-7 nm diameter range. 46 These results are in accordance with the study of Morozov and coworkers developed in 1975, where they have observed the same crystallographic change (from hcp to fcc) in nanoparticles with ;20 nm diameter, which also lead to the disappearance of any magnetic ordering above 2 K. 47 The oxidation typically observed in Gd nanoparticles appears to have been greatly reduced by Ertas and coworkers who have recently developed a novel nanofabrication route based on nanosphere lithography combined with the metal reduction process. This technique resulted in the production of oxide-free Gd nanoparticles, with tunable size and monodisperse nature (up to 5%), high magnetization (206 emu/g at 2 K), and great potential in magnetic resonance imaging.…”
Section: Magnetocaloric Systemssupporting
confidence: 89%
“…More interestingly, they have shown a size-induced structural transformation from the hexagonal (typical of bulk Gd) to a cubic fcc structure in the 5-7 nm diameter range. 46 These results are in accordance with the study of Morozov and coworkers developed in 1975, where they have observed the same crystallographic change (from hcp to fcc) in nanoparticles with ;20 nm diameter, which also lead to the disappearance of any magnetic ordering above 2 K. 47 The oxidation typically observed in Gd nanoparticles appears to have been greatly reduced by Ertas and coworkers who have recently developed a novel nanofabrication route based on nanosphere lithography combined with the metal reduction process. This technique resulted in the production of oxide-free Gd nanoparticles, with tunable size and monodisperse nature (up to 5%), high magnetization (206 emu/g at 2 K), and great potential in magnetic resonance imaging.…”
Section: Magnetocaloric Systemssupporting
confidence: 89%
“…Similar anomalies have been detected also in FMP of terbium and of holmium. 29 Earlier, a cubic modification of gadolinium and of other rare-earth elements was also detected by electron diffraction in thin films of thickness less than 15 nm. The structure of films of thickness greater than 20 nm was identified as a mixture of hep and fee phases.…”
Section: C) Structural Transformationsmentioning
confidence: 94%
“…27 Gadolinium FMP have been investigated in the size range from 110 to 24 nm. 28 X-ray structural investigations showed that their structure depends on the size of the particles and differs sharply from the structure of bulk crystals. In bulk specimens of gadolinium, under normal conditions, the structure corresponds to the hep lattice.…”
Section: C) Structural Transformationsmentioning
confidence: 99%